Global stability analysis of an SVEIR epidemic model with general incidence rate - Da-peng Gao; Nan-jing Huang; Shin Min Kang; Cong Zhang (Boundary Value Problems, 2018)
Abstract In this paper, a susceptible-vaccinated-exposed-infectious-recovered (SVEIR) epidemic model for an infectious disease that spreads in the host population through horizontal transmission is investigated, assuming that the horizontal transmission is governed by an unspecified function f(S,I) $f(S,I)$. The role that temporary immunity (vaccinated-induced) and treatment of infected people play in the spread of disease, is incorporated in the model. The basic reproduction number R0 $\mathcal{R}_{0}$ is found, under certain conditions on the incidence rate and treatment function. It is shown that the model exhibits two equilibria, namely, the disease-free equilibrium and the endemic equilibrium. By constructing a suitable Lyapunov function, it is observed that the global asymptotic stability of the disease-free equilibrium depends on R0 $\mathcal{R}_{0}$ as well as on the treatment rate. If R0>1 $\mathcal{R}_{0}>1$, then the endemic equilibrium is globally asymptotically stable with the help of the Li and Muldowney geometric approach applied to four dimensional systems. Numerical simulations are also presented to illustrate our main results.